Effect of ongoing inflammation in rheumatoid arthritis on P-wave dispersion - Yavuzkir, M.; Ozturk, A.; Dagli, N.; Koca, S.; Karaca, I.; Balin, M.; Isik, A. (Sage Publications Ltd, 2007)
It has been emphasized recently that there is a strong association between atrial fibrillation and inflammation. Rheumatoid arthritis (RA), characterized by ongoing inflammatory activity, can increase the risk of atrial arrhythmia. P-wave dispersion has been encountered as a risk factor for atrial fibrillation and the effect of inflammation on P-wave dispersion has not been studied thoroughly. The aim of this study was to examine the effect of ongoing inflammatory activity in RA on P-wave dispersion. The study comprised 82 patients diagnosed with RA and 41 healthy volunteers as controls. Systolic functions of all participants were evaluated by echocardiography. Maximum P-wave duration and dispersion were calculated and found to be significantly increased in the RA group compared with the healthy controls. These parameters were also significantly correlated with C-reactive protein levels. The findings of this study suggest that RA may be associated with increases in P-wave dispersion and maximum P-wave duration, and that this association may result from ongoing inflammation.
Keywords: rheumatoid arthritis; inflammation; P-wave dispersion; P-wave duration; C-reaction protein